2020
DOI: 10.1108/sej-07-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

Fostering social capital: the case of community-owned pubs

Abstract: Purpose This paper aims to examine the relationship between community-owned enterprises and social capital in urban neighbourhoods. Focussing on community-owned pubs (COPs), the paper investigates how social capital elements have a role in generating these innovative organizations, which foster benefits for community members. Design/methodology/approach This qualitative research based on data gathered through 23 semi-structured interviews, in an in-depth case study analysis of three COPs located in Carshalto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Pubs have been shown to play an important role in providing spaces in which local individuals and group can meet, interact and forge and maintain social bonds (Cabras and Mount 2017). For example, recent research by Sforzi and Bianchi (2020) examines community owned pubs in three areas of London to show that such venues help create bonding social capital, between those involved in the pub ownership, and bridging social capital, between those directly involved in the pub and the wider community of local residents.…”
Section: Getting Social Down the Local?mentioning
confidence: 99%
“…Pubs have been shown to play an important role in providing spaces in which local individuals and group can meet, interact and forge and maintain social bonds (Cabras and Mount 2017). For example, recent research by Sforzi and Bianchi (2020) examines community owned pubs in three areas of London to show that such venues help create bonding social capital, between those involved in the pub ownership, and bridging social capital, between those directly involved in the pub and the wider community of local residents.…”
Section: Getting Social Down the Local?mentioning
confidence: 99%
“…Our literature review has confirmed that the public sphere cannot function well in atomised, broken, distrustful, and insecure societies, where social capital is lacking. In recent years, the concept of social capital, broadly defined as cooperative networks based on regular communication and trust, has been applied within cross-disciplinary social science research, primarily by sociologists, political scientists, and economists, of which the most notable are: Putnam, Bourdieu, and Fukuyama [13][14][15][56][57][58].…”
Section: Bridging Social Capital and The Factors Affecting Its Level ...mentioning
confidence: 99%
“…Social enterprises use a business model to promote and sustain social goals, often employing people who face significant barriers to traditional employment (Social Enterprise Alliance, 2021). Studies have found community‐owned social enterprise fosters social capital in urban communities by encouraging trust and common purpose among residents in the community (Sforzi & Bianchi, 2020). Community advocates and residents called for solutions that involve racial representation and focus on meeting the needs of existing community members.…”
Section: Discussionmentioning
confidence: 99%